Honey bee Royalactin unlocks conserved pluripotency pathway in mammals. Issue 1 (December 2018) - Wan, Derrick; Morgan, Stefanie; Spencley, Andrew; Mariano, Natasha; Chang, Erin; Shankar, Gautam; Luo, Yunhai; Li, Ted; Huh, Dana; Huynh, Star; Garcia, Jasmine; Dovey, Cole; et al.
Abstract Royal jelly is the queen-maker for the honey beeApis mellifera, and has cross-species effects on longevity, fertility, and regeneration in mammals. Despite this knowledge, how royal jelly or its components exert their myriad effects has remained poorly understood. Using mouse embryonic stem cells as a platform, here we report that through its major protein component Royalactin, royal jelly can maintain pluripotency by activating a ground-state pluripotency-like gene network. We further identify Regina, a mammalian structural analog of Royalactin that also induces a naive-like state in mouse embryonic stem cells. This reveals an important innate program for stem cell self-renewal with broad implications in understanding the molecular regulation of stem cell fate across species. Royal jelly is the queen-maker for the honey bee that also has effects on longevity, fertility, and regeneration in mammals. Here the authors provide evidence that its major protein component Royalactin, and the mammalian structural analog Regina, maintain pluripotency in mouse ESCs by activating a ground-state pluripotency-like gene network.